Nanostructured materials for glyphosate capture—A mini-review - Vargas-Delgadillo, Diana P.; Giraldo, Liliana; Moreno-Piraján, Juan Carlos (Frontiers in Sustainability, 2022)
Water is an essential part of life, and its availability is important for all living purposes, due to industrial development and the high demand for agricultural products that humans require for their survival, it has produced a high level of environmental pollution, which has generated a problem in recent decades. Among the large number of pollutants that have been found in wastewater is the glyphosate molecule (Gly), the most widely used as an herbicide for agriculture. within this context, this minireview summarizes the current advances and discussions on the development of nanomaterials, focusing their application to capture the glyphosate molecule and thus improve wastewater treatment. metallic organic frameworks structures, graphene’s, and porous organic solids are among the most versatile porous materials that have been extensively investigated for application in glyphosate capture. Under this context, the intention of the following review is providing and summarizing a discussion of a research advances recent in the capture of glyphosate, from wastewater using nanostructured materials.